Building multimedia repository for composing images perspective - Samir Elloumi (14152470) (2019)
Multimedia repository is helpful for educational activities since it offers several illustrations that facilitate the learning process and the text understanding. In this paper, we propose to build a multimedia repository from collected images using object extraction techniques. Then, we associate Arabic captions to all extracted objects. These extracted objects are used to compose new scenes that could illustrate efficiently the most important events in an Arabic story. We extend, thereby the notion of image composing to our approach as the task of constructing new images based on a set of toolboxes and a set of extracted objects as our multimedia repository of common animal behaviors. Our preliminary results show that the composed scenes using single objects provided a fair understanding of the main events of the stories as well as a coherent visual layout of all single objects. The diversity and the precision of the single objects images for the domain of animals have shown a great impact on composing new scenes either manually or dynamically. Other Information Published in: SN Applied Sciences License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s42452-019-1123-y